2001
DOI: 10.1104/pp.010421
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Functional Analysis of Homogentisate Phytyltransferase from Synechocystis sp. PCC 6803 and Arabidopsis

Abstract: Tocopherols, collectively known as vitamin E, are lipid-soluble antioxidants synthesized exclusively by photosynthetic organisms and are required components of mammalian diets. The committed step in tocopherol biosynthesis involves condensation of homogentisic acid and phytyl diphosphate (PDP) catalyzed by a membrane-bound homogentisate phytyltransferase (HPT). HPTs were identified from Synechocystis sp. PCC 6803 and Arabidopsis based on their sequence similarity to chlorophyll synthases, which utilize PDP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(109 citation statements)
references
References 43 publications
3
106
0
Order By: Relevance
“…Transgenic plants and mutants with altered expression of different enzymes of tocopherol biosynthesis have been created and tested under stress conditions, and represent new tools with which to investigate regulation of and by tocopherols (e.g. Shinatani and DellaPenna 1998;Tanaka et al 1999;Collakova and DellaPenna 2001;Graßes et al 2001). Transgenic plants with altered amounts of TAT are underway and are currently being tested in order to elucidate the role of TAT in tocopherol biosynthesis and the role of tocopherols under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic plants and mutants with altered expression of different enzymes of tocopherol biosynthesis have been created and tested under stress conditions, and represent new tools with which to investigate regulation of and by tocopherols (e.g. Shinatani and DellaPenna 1998;Tanaka et al 1999;Collakova and DellaPenna 2001;Graßes et al 2001). Transgenic plants with altered amounts of TAT are underway and are currently being tested in order to elucidate the role of TAT in tocopherol biosynthesis and the role of tocopherols under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, at the amino acid level AuaA shares sequence similarities of 34.5 % with MenA (biosynthesis of menaquinone), [11] and 25.3 % with UbiA (biosynthesis of ubiquinone), [10] both from E. coli. AuaA also shows sequence similarities to membrane-bound prenyltransferases from plants, for example, 27.1 % to HPT from Arabidopsis thaliana [28] and 26.7 % to LePGT1 from Lithospermum erythrorhizon. [29] For expression in E. coli, auaA was amplified from genomic DNA and cloned in pQE60 to result in the expression construct pES19.…”
Section: Sequence Analysis Gene Cloning and Protein Overexpressionmentioning
confidence: 93%
“…However, Synechocystis mutants with impaired tocopherol biosynthesis survive under both optimal and high light conditions in the absence of tocopherols (Collakova and DellaPenna 2001;Da¨hnhardt et al 2002). In another study, an A. thaliana mutant totally devoid of tocopherols, vte1, showed a growth reduction of only 10-15% and small reductions in chlorophyll content and photosynthetic quantum yield when exposed to a light intensity of 850 lmol photons m )2 s )1 (Porfirova et al 2002).…”
mentioning
confidence: 94%
“…However, only tocopherol biosynthesis is impaired by a defect in the hpd gene in Synechocystis, thus suggesting an alternative plastoquinone biosynthetic pathway in this cyanobacterium . Moreover, it has been shown that different polyprenyltransferases are required for the synthesis of tocopherols and plastoquinones both in cyanobacteria and higher plants (Collakova and DellaPenna 2001;Schledz et al 2001;Savidge et al 2002). After the prenylation of homogentisic acid, three further enzymatic modifications occur, including two methylation reactions and a cyclization reaction forming the chromanol head group (Porfirova et al 2002).…”
mentioning
confidence: 99%